IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT BY USING STUDENT TEAM ACHIEMENT DIVISIONS (STAD) TECHNIQUE - Rossanna Sriwahyuni (Universitas Negeri Medan, 2014)
This study was focused on the improvement of Grade VIII students’ writing achievement in descriptive text by using application of STAD Technique. The objective of this study was to find out whether STAD Technique could improve Grade VIII students’ writing achievement in descriptive text. The study conducted by using Class Room Action Research ( CAR ). The subjects of this study were students of Grade VIII Class 2 of State Junior High School ( Sekolah Menengah Pertama) SMP PAB 10 Medan consisting of 23 students. The study was implemented in two cycle and each cycle consisted of three meeting. The instruments of data collection consisted of quantitative and qualitative data. The quantitative data were taken from students written test and the qualitative were taken from the interview, diary notes, observation sheet and questionnaire. Based on the descriptive writing result, students score in the test of cycle I, the mean score was 68,4 and it the test of Cycle II was 76,9. Based on the observation sheet, it was found that the teaching-learning process well done. The students were active and curious in writing. In line with the data, it found that STAD ( Students Team Achievement Divisions) technique can improve Grade VIII students’ writing achievement in descriptive text. The Key : Writing Descriptive by Using STAD Technique and Classroom Action Research Method